INVESTIGATION OF LOGISTIC PERFORMANCE OF G-20 COUNTRIES USING DATA ENVELOPMENT ANALYSIS AND MALMQUIST TOTAL FACTOR PRODUCTIVITY ANALYSIS - Ömür Tosun; Nesrin Koç Ustalı (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study aims to make a comparative efficiency analysis of G-20 countries in terms of logistics performance. For this purpose, evaluation criteria have been determined with the help of industry and academic expert opinion and data set of evaluation criteria were obtained from the World Bank database. In this study, the analysis was made according to the CCR and the BCC input-based models by the Data Envelopment Analysis method. First, the efficiency scores of the countries were determined. After, reference groups were determined for the countries under the efficient frontier. Then, analyzes were made to find potential improvement values for the countries under the efficient frontier. Besides, Malmquist Total Factor Productivity Analysis was made in order to determine the efficiency change of countries in the 2007-2016 period. According to the results of the study, it has been determined that the country efficiency values and reference groups differed years. Moreover, it was determined that the most productive period is 2007-2010 and the most inefficient period is 2010-2012. Also, it has been observed that China and India have continuously improved in terms of efficiency types.